2018
DOI: 10.1038/s41598-018-29051-z
|View full text |Cite
|
Sign up to set email alerts
|

Rational quantum secret sharing

Abstract: The traditional quantum secret sharing does not succeed in the presence of rational participants. A rational participant’s motivation is to maximize his utility, and will try to get the secret alone. Therefore, in the reconstruction, no rational participant will send his share to others. To tackle with this problem, we propose a rational quantum secret sharing scheme in this paper. We adopt the game theory to analyze the behavior of rational participants and design a protocol to prevent them from deviating fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The comparison of results among the protocols is shown in Table 1. Deng et al [15] No No --Maitra et al [37] Yes Yes Yes No Qin et al [39] Yes Yes -No Dou et al [38] Yes For the first condition "Whether the players are rational", from a practical perspective, a player should be rational. In a rational protocol, a player will choose to participate in the protocol honestly or dishonestly based on his own utility.…”
Section: Comparison Of Results Among Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of results among the protocols is shown in Table 1. Deng et al [15] No No --Maitra et al [37] Yes Yes Yes No Qin et al [39] Yes Yes -No Dou et al [38] Yes For the first condition "Whether the players are rational", from a practical perspective, a player should be rational. In a rational protocol, a player will choose to participate in the protocol honestly or dishonestly based on his own utility.…”
Section: Comparison Of Results Among Protocolsmentioning
confidence: 99%
“…In 2018, Dou et al [38] proposed a rational QSTS (RQSTS) protocol with the online dealer. Qin et al [39] proposed an RQSTS protocol based on the quantum Fourier transform.…”
Section: Introductionmentioning
confidence: 99%
“…The Au, Ag nanostructures materials are more likely to enhance the EMF in a broad range from UV-vis to NIR, which gives more superiority in this field. [45] For instance, it has been reported that gold-loaded titanium dioxide (Au-TiO 2 ) heterostructures, [45] large Pt NPs supported on TiO 2 hierarchical nano-architecture (Pt/TiO 2 -HA) photocatalysts, [93] Janus Au-TiO 2 photocatalysts outperform visible-light H 2 generation. These observations have been attributed to the enhanced optical absorption of TiO 2 itself that is caused by the strongly enhanced EMFs of the surrounded Au NPs, contributing to improving the electron-hole generation inside the TiO 2 semiconductor.…”
Section: Local Emf Enhancementmentioning
confidence: 99%
“…The existence of stochastic equilibria with imprecise deviations for CSGs and a PSPACE algorithm to compute such equilibria is considered in [8]. Finally, we mention the fact that the concept of equilibrium is used to analyze different applications such as cooperation among agents in stochastic games [39] and to design protocols based on quantum secret sharing [67].…”
Section: Introductionmentioning
confidence: 99%